(7x - 12)²=2⁵ . 5² + 200
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`(7x-11)^3 =5^2 *2^5 +200`
`=>(7x-11)^3 =25*32+200`
`=>(7x-11)^3 =800+200`
`=>(7x-11)^3 =1000`
`=>(7x-11)^3 =10^3`
`=>7x-11=10`
`=>7x=10+11`
`=>7x=21`
`=>x=21:7`
`=>x=3`
chuyển đổi lại : (7x - 3) : 12 = 13
=> (7x - 3) = 13 * 12
=> 7x - 3 = 156
=> 7x = 159
=> x= 159/7
[(7x - 31) : 5] * 36 = 7236
=> [(7x - 31) : 5] = 7236 : 36 = 201
=> (7x - 31) : 5 = 201
=> 7x - 31 = 1005
=> 7x = 1036
=> x = 148
1 + 2 + 3 + 4 + 5 +... + 100 + x = 5350
SSH : \(\left(100-1\right):1+1=100\)
=> tổng : \(\frac{\left(1+100\right)\cdot100}{2}=5050\)
=> 5050 + x = 5350
=> x = 5350 - 5050 = 300
80 - 9(x - 4) = 35
=> 9(x - 4) = 80 - 35 = 45
=> x - 4 = 45 : 9
=> x - 4 = 5
=> x = 9
(3x - 21) : 4 + 108 = 114
=> (3x - 21) : 4 = 114 - 108 = 6
=> 3x - 21 = 24
=> 3x = 45
=> x = 15
[(6x - 72) : 2 - 84]*14 = 2814
=> [(6x - 72) : 2 - 84] = 201
=> (6x - 72) : 2 - 84 = 201
=> (6x - 72) : 2 = 285
=> 6x - 72 = 570
=> 6x = 642
=> x = 107
28x + 12x = 80
=> 40x = 80
=> x = 2
249 - 7(1 + x) = 200
=> 7(1 + x) = 49
=> 1 + x = 7
=> x = 6
20 - [(x - 5) * 7 + 4] = 2
=> [(x - 5) * 7 + 4] = 18
=> (x - 5)*7 + 4 = 18
=> (x - 5) * 7 = 14
=> x - 5 = 2
=> x = 7
\(\frac{7x-33}{12}=13\)
\(7x-33=13\cdot12\)
\(7x-33=156\)
\(7x=156+33\)
\(7x=189\)
\(x=\frac{189}{7}=27\)
\(\frac{7x-31}{5}\cdot36=7236\)
\(\frac{7x-31}{5}=\frac{7236}{36}\)
\(\frac{7x-31}{5}=201\)
\(7x-31=201\cdot5\)
\(7x-31=1005\)
\(7x=1005+31\)
\(7x=1036\)
\(x=\frac{1036}{7}=148\)
\(1+2+3+4+5+..+100+x=5350\)
\(\left(1+2+3+4+5+...+100\right)+x=5350\)
Phần 1 + 2 + 3 + 4 + 5 + ... + 100 có số số hạng là :
\(\frac{100-1}{1}+1=100\) ( số hạng )
\(\Rightarrow\frac{\left(100+1\right)\cdot100}{2}+x=5350\)
\(5050+x=5350\)
\(x=5350-5050=300\)
\(80-9\left(x-4\right)=35\)
\(9\left(x-4\right)=80-35\)
\(9\left(x-4\right)=45\)
\(x-4=\frac{45}{9}\)
\(x-4=5\)
\(x=5+4=9\)
\(\frac{3x-21}{4}+108=114\)
\(\frac{3x-21}{4}=114-108\)
\(\frac{3x-21}{4}=6\)
\(3x-21=6\cdot4\)
\(3x-21=24\)
\(3x=24+21\)
\(3x=45\)
\(x=\frac{45}{3}=15\)
\(14\left(\frac{6x-72}{2}-84\right)=2814\)
\(3x-36-84=\frac{2814}{14}\)
\(3x-120=201\)
\(3x=201+120\)
\(3x=321\)
\(x=\frac{321}{3}=107\)
\(28x+12x=80\)
\(x\left(28+12\right)=80\)
\(x\cdot40=80\)
\(x=\frac{80}{40}=2\)
\(249-7\left(1+x\right)=200\)
\(-7\left(1+x\right)=200-249\)
\(-7\left(1+x\right)=-49\)
\(1+x=\frac{-49}{-7}\)
\(1+x=7\)
\(x=7-1=6\)
\(20-7\left(x-5\right)+4=2\)
\(20-7\left(x-5\right)=2-4\)
\(20-7\left(x-5\right)=-2\)
\(-7\left(x-5\right)=-2-20\)
\(-7\left(x-5\right)=-22\)
\(x-5=\frac{-22}{-7}\)
\(x=\frac{22}{7}+5=\frac{57}{7}\)
Ta có:(7x-11)3=25 * 52 + 200
=> (7x-11)3=32 * 25 + 200
=> (7x-11)3=800 + 200
=> (7x-11)3=1000 = 103
=> 7x-11 = 10
=> 7x = 21
=> x = 3
(7x - 11 )^3 = 32*25+200
(7x - 11 ) ^3 = 1000
(7x-11)^3 = 10^3
=> 7x - 11 = 10 => 7x = 11 + 10 = 21 => x = 21 : 7 => x = 3
1) \(\left(5+x\right)^2-36=0\)
\(\Rightarrow\left(5+x-6\right)\left(5+x+6\right)=0\Rightarrow\left(x-1\right)\left(x+11\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x=1\\x=-11\end{matrix}\right.\)
2) \(\Rightarrow\left(7x-11\right)^3=1000=10^3\)
\(\Rightarrow7x-11=10\Rightarrow7x=21\Rightarrow x=3\)
\(\Rightarrow\left(7x-11\right)^3=\left(2\cdot5\right)^5+200=10^5+200\\ \Rightarrow\left(7x-11\right)^3=10000+200=10200\\ \Rightarrow7x-11=\sqrt[3]{10200}\\ \Rightarrow x=\dfrac{\sqrt[3]{10200}+11}{7}\)
( 7x - 11 )3 = 32 . 25 + 200
( 7x - 11 )3 = 800 + 200
( 7x - 11 )3 = 1000
( 7x - 11 )3 = 103
=> 7x - 11 = 10
7x = 10 + 11
7x = 21
x = 21 : 7
x = 3
\(\left(7x-12\right)^2=2^5.5^2+200\)
\(\left(7x-12\right)^2=25.32+200\)
\(\left(7x-12\right)^2=800+200\)
\(\left(7x-12\right)^2=1000=\left(10\sqrt{10}\right)^2\)
\(\Leftrightarrow\left[{}\begin{matrix}7x-12=10\sqrt{10}\\7x-12=-10\sqrt{10}\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{10\sqrt{10}+12}{7}\\x=\dfrac{12-10\sqrt{10}}{7}\end{matrix}\right.\)